Return to ovulation after Sayana Press is injected every 4 months for one year: Empirical and pharmacokinetic/pharmacodynamic modeling results - Douglas J. Taylor; Jennifer Deese; Luis Bahamondes; Vivian Brache; Nelio Veiga, Jr; Rachael Fuchs; Vera Halpern; Laneta J. Dorflinger (Elsevier, 2022)
Objective: To characterize return to ovulation after injecting Sayana Press (104 mg/0.65 mL medroxyprogesterone acetate [MPA] in the Uniject device) every 4 months for 1 year of treatment. Study design: We followed a subset of women for return to ovulation in a trial that demonstrated Sayana Press remains highly effective when the subcutaneous reinjection interval is extended from 3 to 4 months. We measured serum progesterone in weeks 38 to 42 and 46 to 50 after a final (third) injection and used a concentration ≥4.7 ng/mL as a surrogate for ovulation. We also performed pharmacokinetic and pharmacodynamic modeling to predict differences in MPA accumulation and return to ovulation had - contrary to fact - injections been given every 3 months. Results: Ten of 19 women (53%; 95% confidence interval: 29-76) ovulated within 50 weeks of their last injection. We predicted that typical 12-month trough MPA concentrations are 34% lower (0.46 vs 0.69 ng/mL) and the median time from last dose to ovulation is 1.1 months shorter (13.1 vs 14.2 months) when injections are given every four months for 1 year. Conclusion: Extending the Sayana Press reinjection interval from 3 to 4 months leads to less drug accumulation, without a noticeable loss in efficacy. Although the Sayana Press patient leaflet specifies that over 80% of women desiring pregnancy will conceive within a year of stopping the method (independent of treatment duration), our empirical and modeling results indicate women should anticipate waiting a year or more for fertility to return after repeat dosing, with a somewhat shorter delay were the reinjection interval extended to four months. Implications: Providers should counsel women regarding the distinct possibility that return to fertility will take a year or longer following repeat use of Sayana Press. Extending the dosing interval from 3 to 4 months would result in approximately a 1-month shorter delay, without any appreciable reduction in contraceptive efficacy.